Pengaruh Kecerdasan Emosional Terhadap Hasil Belajar Pendidikan Jasmani pada Masa Pandemi - Mardius, Ali; Enjoni, Enjoni; Fuadi, Al Busyra (JURNAL MUARA OLAHRAGA, 2022)
Abstract This study aims to determine the effect of Emotional Intelligence on physical education learning outcomes during the pandemic. This type of quantitative research uses a correlation research design with a causal associative method. The population in this study amounted to 62 people. The sampling technique used total sampling technique, which is a sampling technique that provides equal opportunities for each element/member of the population to be selected as a member of the sample, while the number of samples in this study was 62 people. Data were collected using a questionnaire. Data were analyzed by multiple regression of two predictors. Based on the results of data analysis shows that: Variable emotional intelligence has a significant effect on learning outcomes of physical education. This means that the higher the emotional intelligence, the better the physical education learning outcomes. Keywords: Emotional Intelligence, Learning Motivation and Learning Outcomes